The ghost forest : racists, radicals, and real estate in the California redwoods - King, Greg (Journalist) (PublicAffairs, 2023)
The definitive story of the California redwoods, their discovery and their exploitation, as told by an activist who fought to protect their existence against those determined to cut them down. Every year millions of tourists from around the world visit California's famous redwoods. Yet few who strain their necks to glimpse the tops of the world's tallest trees understand how unlikely it is that these last isolated groves of giant trees still stand at all. In this gripping historical memoir, journalist and famed redwood activist Greg King examines how investors and a growing U.S. economy drove the timber industry to cut down all but 4 percent of the original two-million-acre redwood ecosystem. King first examined redwood logging in the 1980s--as an award-winning reporter. What he found in the woods convinced him to leap the line of neutrality and become an activist dedicated to saving the very last ancient redwood groves remaining in private hands. The land grab began in 1849, when a "green gold rush" of migrants came to exploit the legendary redwoods that grew along the Russian River. Several generations later, in 1987, Greg King discovered and named Headwaters Forest--at 3,000 acres the largest ancient redwood habitat remaining outside of parks--and he led the movement to save this grove. After a decade of one of the longest, most dramatic, and violent environmental campaigns in US history, in 1999 the state and federal governments protected Headwaters Forest. The Ghost Forest explores a central question, an overhanging mystery: What was it like, this botanical Elysium that grew only along the Northern California coast, a forest so spectacular--but also uniquely valuable as a cornerstone of American economic growth--that in the end it would inspire life-and-death struggles? Few but loggers and surveyors ever saw such magnificent trees, ancient sentinels that, like ghosts, have informed King's understanding of the world. On a lifelong journey, King finds himself through the generations, and through the trees.